Navigating the Digital Marketplace: A Holistic Model Integrating Social Media Engagement and Consumer Behavior Factors to Enhance Online Shopping Adoption - Murshed, Nasr Abdulaziz; Ugurlu, Erginbay (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2023)
Objective: This study aims to explore the intricacies of online consumer behavior in Yemen and build a model to drive online shopping adoption by investigating the relationships among various factors - including social media engagement, awareness, social cognition, online business perception, perceived price value, usability, and adoption intention - within the Yemeni context. Design/Methods/Approach: Employing a quantitative research framework, this study utilized established scales adapted to Arabic. A structural equation model was developed using Amos 25 to test hypothesized causal relationships among the variables. Data collection was done through an online survey distributed to social media users in Yemen between May and October 2022. Statistical power calculations confirm a robust sample size of 395 participants for the study SEM model. Findings: Correlation analysis revealed strong relationships between various factors, highlighting online business perception’s substantial correlation with adoption intention. Structural equation modeling unveiled significant associations, indicating the positive impact of social cognition on social media engagement, the interconnectedness of awareness, social cognition, usability, and adoption intention, and the influential role of perceived price value in adoption intentions. The research also identified indirect effects and moderating influences, particularly related to prior online shopping experiences. Originality/Value: This research significantly contributes by being among the pioneering studies to delve into consumer behavior and online business in Yemen. It offers unique insights into the role of social media engagement in driving online shopping adoption, filling a critical gap in understanding consumer behavior within the Yemeni context. These findings contribute to the broader literature on e-commerce, particularly in regions where online shopping practices are emerging. Practical/Policy implication: The study’s findings emphasize the interconnected nature of various online shopping behavior factors, necessitating a holistic approach in business strategies. Businesses can leverage robust social media engagement to drive targeted marketing strategies, acknowledging its pivotal role in shaping consumer behavior towards online shopping. Focusing on enhancing visibility and promoting awareness of products/services is crucial. Moreover, investing in user-friendly interfaces, delivering positive online business experiences, offering competitive prices, and effectively communicating value propositions are key strategies to bolster adoption intentions.